Role of integrated approach in the management of Asthma: A case study - ANJALI MUKERJEE, (International Journal of Pharma and Bio Sciences, 2018)
Asthma is a common chronic inflammatory obstructive lung disease that affects persons of all ages. The treatment options currently available aim to alleviate symptoms, improve quality of life and prevent disease progression rather than addressing the root cause and the underlying condition itself. As opposed to a palliative approach, an alternative, holistic therapy addresses not only the constellation of symptoms associated with asthma, but also treats the underlying cause(s), such that the patient gets long-lasting symptomatic relief, overall health improvement and improved disease outcome. One such is the ‘Integrated Approach’ that uses food as medicine and combines the benefits of ayurvedic, herbal, nutritional therapy, vitamins and dietary supplements, therapeutic lifestyle changes and simple exercise. Such a holistic approach is both preventive and therapeutic in supporting health and reduces risk of diet-related diseases. The subject of this study is a 11-year-old-girl with a clinical history of asthma along with sleeping difficulties, dry skin and white patches on the chin, poor appetite, underweight status and constipation. The patient started treatment with an integrated approach. This paper describes in detail the utilization of the ‘Integrated Approach’ in the management of asthma and associated conditions and improvement in the patient’s condition while on this treatment regimen. During the 4-month treatment, significant improvement was observed in the patient’s asthma and her asthma attacks were found to be milder. Additionally, her bowel movements improved and she started gaining weight.